Economics and Law - Mitrofanova M. I., Blinkov S. N., Levushkin S. P., Kosikhin V. P., Miasoedov C. A., Kashirtseva A. I., Plakhotnikova M. A., Zhoglicheva V. V., Taniushcheva N. I., Globa M. V., Kugai A. I. (Economics and Law, 2021)
the main features of the development of the mineral resource complex of the Russian Federation in the field of development of deposits of a number of metals are summarized; management tools for the mineral resource complex of a number of metal-producing industries of the Russian Federation are grouped; target settings for ensuring the sustainable development of metal-producing industries are formulated; a system of cluster management of the mineral-raw complex of metal-producing industries of the Russian Federation is proposed
Keywords: экономика; economy; устойчивое развитие; sustainable development; промышленная политика; горнодобывающая промышленность; mining industry; industrial policy